Genome and proteome analyses show the gaseous alkane degrader Desulfosarcina sp. strain BuS5 as an extreme metabolic specialist. (7th March 2022) - Chen, Song‐Can; Ji, Jiaheng; Popp, Denny; Jaekel, Ulrike; Richnow, Hans‐Hermann; Sievert, Stefan M.; Musat, Florin
Summary: The metabolic potential of the sulfate‐reducing bacterium Desulfosarcina sp. strain BuS5, currently the only pure culture able to oxidize the volatile alkanes propane and butane without oxygen, was investigated via genomics, proteomics and physiology assays. Complete genome sequencing revealed that strain BuS5 encodes a single alkyl‐succinate synthase, an enzyme which apparently initiates oxidation of both propane and butane. The formed alkyl‐succinates are oxidized to CO2 via beta oxidation and the oxidative Wood–Ljungdahl pathways as shown by proteogenomics analyses. Strain BuS5 conserves energy via the canonical sulfate reduction pathway and electron bifurcation. An ability to utilize long‐chain fatty acids, mannose and oligopeptides, suggested by automated annotation pipelines, was not supported by physiology assays and in‐depth analyses of the corresponding genetic systems. Consistently, comparative genomics revealed a streamlined BuS5 genome with a remarkable paucity of catabolic modules. These results establish strain BuS5 as an exceptional metabolic specialist, able to grow only with propane and butane, for which we propose the name Desulfosarcina aeriophaga BuS5. This highly restrictive lifestyle, most likely the result of habitat‐driven evolutionary gene loss, may provide D. aeriophaga BuS5 a competitive edge in sediments impacted by natural gas seeps. Etymology: Desulfosarcina aeriophaga, aério (Greek): gas; phágos (Greek): eater; D. aeriophaga : a gas eating or gas feeding Desulfosarcina .